2001
DOI: 10.1046/j.1460-9592.2001.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Prevalence of Complicated Atrial Arrhythmias, Flutter, and Fibrillation in Patients with Reciprocating Supraventricular Tachycardia Before and After Successful Catheter Ablation

Abstract: Atrial flutter and AF are complications in approximately 30% of cases of paroxysmal supraventricular tachycardia (PSVT)-indicated catheter ablation, and it is of interest to determine if therapeutic modification for PSVT would eliminate combined atrial tachyarrhythmia like atrial flutter and AF. The aim of this study was to determine the incidence and the risk of atrial tachyarrhythmias after catheter ablation of PSVT. A total of 152 patients (age range 12-74, mean 41 +/- 17 years) with accessory pathway (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(21 reference statements)
1
7
0
1
Order By: Relevance
“…If atrioventricular accessory pathways were the sole contributor of clinical AF in patients with WPW, elimination of the accessory pathway would have prevented AF in all patients. Our study showed that the recurrence rate of symptomatic AF after successful catheter ablation of accessory pathways was 11%, which was consistent with the previous findings from other groups (8–11). These data show that the mechanisms of symptomatic AF in patients with atrioventricular accessory pathways are complex; accessory pathways and accessory pathway‐mediated supraventricular tachycardia are only one part of the many potential causes of clinical AF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…If atrioventricular accessory pathways were the sole contributor of clinical AF in patients with WPW, elimination of the accessory pathway would have prevented AF in all patients. Our study showed that the recurrence rate of symptomatic AF after successful catheter ablation of accessory pathways was 11%, which was consistent with the previous findings from other groups (8–11). These data show that the mechanisms of symptomatic AF in patients with atrioventricular accessory pathways are complex; accessory pathways and accessory pathway‐mediated supraventricular tachycardia are only one part of the many potential causes of clinical AF.…”
Section: Discussionsupporting
confidence: 93%
“…Although the specific role of accessory atrioventricular pathway in the pathogenesis of AF is not clear, surgical or catheter ablation of accessory pathways often reduces the episodes of spontaneous AF (6–12). However, up to 24% of the patients who had a history of spontaneous AF still experience clinical AF after surgical or radiofrequency catheter ablation of the accessory pathways (7–12). It is poorly understood why some patients still suffer from clinical AF after the elimination of the atrioventricular accessory pathways, but older age or electrophysiologically unstable atrium may be responsible for the recurrence of AF (8–11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, one of the most important findings of this study is that patients with AF recurrence after the elimination of APs is more commonly documented in AT prior to ablation. Miyamoto et al [20] reported a correlation of premature atrial complexes prior to ablation of atrioventricular nodal reciprocating tachycardia (AVNRT) or AP and higher recurrences of AF after a successful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that following successful surgical dissection of APs, there is an almost complete elimination of paroxysmal AF; however, the patients in these studies were young [15][16][17]. Less information exists concerning RFCA due to the enrollment of small groups of patients in previous studies and a short follow-up period [18][19][20].…”
Section: Introductionmentioning
confidence: 99%